Study on the plasticiser type for biobased microcrystalline cellulose filled polylactic acid composite - Pang, Ming Meng; Koay, Seong Chun; Low, Jiun Hor; Buys, Yose Fachmi; Tshai, Kim Yeow (Institute of Physics Publishing, 2018)
The aim of this work was to study the effect of different type of plasticisers, i.e., polyethylene glycol (PEG) and coconut oil (CO), on the properties of microcrystalline cellulose (MCC) filled polylactic acid (PLA) composite. The sample compounding was carried out via melt blending method. The properties of the plasticised MCC filled PLA composites were characterized by tensile, thermal gravimetric analysis (TGA) and scanning electron microscopy (SEM). It was found that CO showed a better plasticising effect, with improvement in elongation at break by 12% as compared to neat PLA and higher decomposition temperature at 302°C.